Accountability of Criminal Perpetrators Who Collectively Misuse Government-Subsidized Oil Fuel Transportation and/or Trading (Study Decision Number 227/Pid.B/LH/2023/PN. Tjk) - Anggalana, Anggalana; Hesti, Yulia; Nabila, Ajeng Surya (QISTINA: Jurnal Multidisiplin Indonesia, 2024)
The factor that causes the perpetrators to commit criminal acts by jointly abusing government-subsidized transportation and/or trading in fuel oil is because the defendant is pressured by economic needs to meet his daily needs, so that he is able to make the defendant act beyond his limits, namely the defendant is able to commit crimes just to make ends meet. his life and the factor of malicious intent is greater where the Defendant does not have good intentions towards Government-subsidized Oil Fuel. And Responsibility for Criminal Perpetrators Collectively Misusing Government-Subsidized Transportation and/or Oil Fuel Trading Based on Decision Number 227/Pid.B/LH/ 2023/PN. Tjk The Defendants were proven to have violated the provisions of Article 55 of Law Number 22 of 2001 concerning Oil and Natural Gas as amended into Republic of Indonesia Law Number 11 of 2020 concerning Job Creation Jo. Article 55 Paragraph (1) 1 of the Criminal Code and is punishable by imprisonment for 8 (eight) months.